Comparing NGS-Based identification of bloodstream infections to traditional culture methods for enhanced ICU care: a comprehensive study - Wang, Wei; Chauhan, Varun; Luo, Yutian; Sharma, Sonu; Li, Chenxi; Chen, Huaisheng (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAccurate identification of infectious diseases using molecular techniques, such as PCR and NGS, is well-established. This study aims to assess the utility of Bactfast and Fungifast in diagnosing bloodstream infections in ICU settings, comparing them against traditional culture methods. The objectives include evaluating sensitivity and specificity and identifying a wide range of pathogens, including non-culturable species.MethodsWe collected 500 non-duplicate blood samples from ICU patients between May 2019 and May 2020. Specimens underwent traditional culture, MALDI-TOF, VITEK®2 compact system, and NGS-based Bactfast and Fungifast analyses.ResultsOut of the 500 samples, 26.8% (n=134) showed bacterial growth via traditional culture methods, while 4.8% (n=24) were positive for fungal growth. MALDI-TOF and VITEK®2 compact system yielded comparable results, identifying 26.4% (n=132) of specimens with bacterial growth. NGS-based Bactfast detected bacterial presence in 38.2% (n=191) of samples, including non-culturable bacteria missed by traditional methods. However, NGS-based Fungifast showed concordant fungal detection rates with culture methods. Among identified pathogens by culture method included Klebsiella pneumoniae 20.89% (n=28), Enterococcus faecalis 18.65% (n=25), Escherichia coli 15.67% (n=21), Pseudomonas aeruginosa 12.68% (n=17), Acinetobacter baumannii 10.44% (n=14), various Streptococcus species 7.46% (n=10), Mycobacterium tuberculosis 6.71% (n=9), Mycobacterium abscessus 4.47% (n=6), and Salmonella spp 2.98% (n=4). Non-culture-based NGS identified additional (n=33) pathogens, including Klebsiella pneumoniae 27.27% (n=9), Bacteroides fragilis 21.21% (n=7), Aerococcus viridans 15.15% (n=5), Elizabethkingia anopheles 12.12% (n=4), Aeromonas salmonicida 9% (n=3), Clostridium 9% (n=3), and Bacteroides vulgatus 6% (n=2). Candida albicans was reported in 5% (n=24) of samples by both methods.ConclusionNGS-based Bactfast and Fungifast demonstrate high sensitivity in identifying a wide array of bacterial and fungal pathogens in ICU patients, outperforming traditional culture methods in detecting non-culturable organisms. These molecular assays offer rapid and comprehensive diagnostic capabilities, potentially improving clinical outcomes through timely and accurate pathogen identification.